Do Pensions Impede Phased Retirement? - William E. Even; David A. Macpherson (Institute for the Study of Labor (IZA), 2004)
Many workers reveal a preference for a gradual reduction in work hours as they approach retirement (?phased retirement?), rather than a sudden change from full-time work to full-time retirement. Pension regulations may impede phased retirement without a switch of employers by prohibiting access to pension assets. This study uses Health and Retirement Survey data to investigate the extent to which a gradual reduction in work hours is made difficult by pensions, particularly defined benefit plans. The study also explores other possible impediments to phased retirement.
Keywords: J32; J26; 330; phased retirement; Flexible Altersgrenze; Gesetzliche Rentenversicherung; Rentenrecht; Ökonomischer Anreiz; Schätzung; Vereinigte Staaten